A photoprotein in mouse embryonic stem cells measures Ca2+ mobilization in cells and in animals. - Silvia Cainarca; Simone Fenu; Cinzia Ferri; Cinzia Nucci; Patrizia Arioli; Andrea Menegon; Lorenzo Piemonti; Stefan Lohmer; Lawrence Wrabetz; Sabrina Corazza (PLoS ONE)
Exogenous expression of pharmacological targets in transformed cell lines has been the traditional platform for high throughput screening of small molecules. However, exogenous expression in these cells is limited by aberrant dosage, or its toxicity, the potential lack of interaction partners, and alterations to physiology due to transformation itself. Instead, primary cells or cells differentiated from precursors are more physiological, but less amenable to exogenous expression of reporter systems. To overcome this challenge, we stably expressed c-Photina, a Ca(2+)-sensitive photoprotein, driven by a ubiquitous promoter in a mouse embryonic stem (mES) cell line. The same embryonic stem cell line was also used to generate a transgenic mouse that expresses c-Photina in most tissues. We show here that these cells and mice provide an efficient source of primary cells, cells differentiated from mES cells, including cardiomyocytes, neurons, astrocytes, macrophages, endothelial cells, pancreatic islet cells, stably and robustly expressing c-Photina, and may be exploited for miniaturized high throughput screening. Moreover, we provide evidence that the transgenic mice may be suitable for ex-vivo bioimaging studies in both cells and tissues.